2013
DOI: 10.7150/ijms.6635
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of RAS Activation and Lipid Disorders Accelerates the Progression of Glomerulosclerosis

Abstract: Background: The activation of the renin-angiotensin system (RAS) and lipid disorders are major risk factors in progressive chronic kidney disease. This study aimed to investigate the potential synergistic mechanisms of RAS activation and lipid disorders that contribute to glomerulosclerosis. Materials and methods: Human renal mesangial cells (HMCs) were treated with 10-7 mol/L angiotensin II (Ang II) or with 30 μg/ml cholesterol and 1 μg/ml 25-hydroxycholesterol (lipid loading) for 24 hours. Lipid accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…When cholesterol deficiency in cells occurs, the ER protein SCAP escorts SREBP-2 from the ER to the Golgi where it cleaves SREBP-2 into nuclear SREBP-2, thus initiating LDLr gene expression (28). Confocal microscopy showed that Ang II stimulation enhanced SCAP/SREBP-2 complex translocation from the ER to the Golgi, suggesting that Ang II is involved in lipid disorder through disrupting the LDLr pathway, which was consistent with our previous studies and those of others (18). Lu et al (29) found that Ang II can increase LDL oxidation and uptake by macrophages, which then promotes the development of atherosclerosis.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…When cholesterol deficiency in cells occurs, the ER protein SCAP escorts SREBP-2 from the ER to the Golgi where it cleaves SREBP-2 into nuclear SREBP-2, thus initiating LDLr gene expression (28). Confocal microscopy showed that Ang II stimulation enhanced SCAP/SREBP-2 complex translocation from the ER to the Golgi, suggesting that Ang II is involved in lipid disorder through disrupting the LDLr pathway, which was consistent with our previous studies and those of others (18). Lu et al (29) found that Ang II can increase LDL oxidation and uptake by macrophages, which then promotes the development of atherosclerosis.…”
supporting
confidence: 91%
“…Our previous studies have verified the positive co‐operative effects of RAS activation with dyslipidaemia in the development of chronic kidney disease and have shown that hyperlipidaemia upregulates the expression of RAS components in the kidney of apolipoprotein gene knockout (ApoE KO) mice and that Ang II stimulation increases cholesterol uptake by mesangial cells through the upregulation of low‐density lipoprotein receptor (LDLr) pathway . However, whether there is a possible interaction of RAS activation with lipid disorder in NAFLD is unknown.…”
mentioning
confidence: 98%
“…Ma et al . reported that Ang II induced lipid accumulation in human renal mesangial cells (HMCs) 21 . Borghi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, plasma levels of LDL cholesterol in patients might be a poor marker for the risk of lipid-mediated organ injuries. The factors affecting lipid redistribution include chronic inflammation [18], decreased glomerular filtration rate [18], activation of the reninangiotensin system [19,20], insulin resistance, and drug administration (e.g. steroids and rapamycin) [10].…”
Section: Discussionmentioning
confidence: 99%